Epidemiological profile of mansoni schistosomiasis cases in the state of Piauí (Research, Society and Development, 2022)
The aim of the present study is to characterize the epidemiological profile of confirmed cases of infection by Schistosoma mansoni in cities in Piauí, Brazil, based on data from compulsory notifications of the parasitosis in the Notifiable Diseases Information System (SINAN), from 1995 to 2017. For this, descriptive retrospective research was performed through the use of secondary epidemiological data. It was possible to survey a total of 44 cases of schistosomiasis mansoni in the state of Piauí. Most people with S. mansoni are of mixed race, 36% (n=9); aged between 20 and 39 years old (48,48%; n=16), 75.76% (n=25) were male; 72.73% lived mainly in urban areas (n=24 cases) and; 24.24% (n=8) had incomplete elementary school only, when considering schooling. Regarding the origin of the cases, 62.5% (n=15 cases) were autochthonous, and most of all cases were cured (87.5%, n=21). The study allowed to know the profile of individuals from Piauí affected by schistosomiasis mansoni. Even though the state is a non-endemic area, it is necessary to pay attention to the disease, since it is a public health problem that is still recurrent and demands of disease control measures.